Central Auditory Pathway Disorders - Kaga, Kimitaka (Springer Japan : Imprint: Springer, 2009)
Brain imaging and neurophysiological methods have been rapidly developed. The purpose of this book is to describe hearing problems which are caused by various kinds of brain diseases in central auditory pathway. Each topic is explained to use a lot of figures such as brain imaging and neurophysiological data comparing with neuropsychological tests. Readers will understand what happens in patients, when bilateral auditory nerve and auditory cortex are damaged in patients. Some patients can hear but cannot discriminate meanings of speech, music and environmental sounds. The author tries to explain why such a difference occurs.